COMBINED METHOD OF SURFACE HARDENING OF HIGH-SPEED STEELS - Kindrachuk, Myroslav; Kharchenko, Volodymyr; Marchuk, Volodymyr; Humeniuk, Ihor; Hlovyn, Mykhailo; Kostetskyi, Ivan (Problems of Friction and Wear, 2023)
The structure, phase and chemical composition, microhardness, and microbrittleness of the surface zones of P6M5 steel after chemical and thermal treatment: nitriding followed by titanium and chromium plating are considered. Metallographic and micro-X-ray spectral analyzes of wear surfaces of P6M5 steel with different types of coating were carried out. It is shown the dependence of physical and mechanical properties of complex coatings and discrete laser treatment on wear-resistance. The analysis of the obtained data showed that azochromic coatings with additional strengthening by laser treatment of steel, which serves as a substrate for coatings, increase its performance in extreme operating conditions, excluding its crushing, chipping and peeling.